Barbara Hannigan conducts and interprets Rossini, Mozart, Ligeti and Fauré - Rossini, Gioacchino 1792-1868; Mozart, Wolfgang Amadeus 1756-1791; Mozart, Wolfgang Amadeus 1756-1791; Mozart, Wolfgang Amadeus 1756-1791; Ligeti, György 1923-2006; Fauré, Gabriel 1845-1924; Ligeti, György 1923-2006 (ACCENTUS Music, 2015)
To be sure, there are pianists who also conduct, and concert masters who lead their orchestra from the violin desk. But a star soprano who coordinates a large instrumental ensemble while at the same time negotiating the trickiest coloratura singing is something entirely new. That is, until Barbara Hannigan came along to reveal this remarkable skill with such high-profile orchestras as the Berlin Philharmonic and the Accademia di Santa Cecilia. "I was never afraid," says the Canadian "artiste étoile," "but now, with this weird conducting thing, I'm really on a path that's my own. It's like walking on virgin snow: there are no footsteps where I'm going." For Ligeti's Mysteries of the Macabre she will also be performing onstage, decked out in an leather bodice and temporarily unable to maintain eye contact with the orchestra. How exactly does that work? It's all a matter of psychology
Keywords: Concertos (Orchestra); Overtures; Songs (High voice) with orchestra; Suites (Orchestra); Internet videos